Treatment of Angio-Seal-Related Femoral Artery Occlusion Using Directional Atherectomy—Primary Results and Midterm Follow-Up. (November 2016) - Babaev, Anvar; Gokhale, Rohit; Zavlunova, Susanna; Attubato, Michael
Objective: We describe a novel approach for the endovascular treatment of femoral artery occlusion as a result of Angio-Seal closure device deployment. Background: Angio-Seal is the most commonly used vascular closure device following percutaneous coronary and peripheral catheterizations worldwide. A rare complication of Angio-Seal deployment is an occlusion of the femoral artery leading to limb ischemia requiring revascularization. Given its unique ability to cut both atherosclerotic plaque and the Angio-Seal anchor with a collagen plug at operator-directed planes, TurboHawk/HawkOne atherectomy device can be a fast and effective approach to treat Angio-Seal-associated femoral artery occlusions. Methods: We studied 13 consecutive patients who developed Angio-Seal-associated femoral artery occlusions that occurred from 3 hours to several weeks after catheterization. These patients were successfully treated with TurboHawk/HawkOne directional atherectomy followed by balloon angioplasty with no complications. During a mean follow-up period of 20.4 ± 17.3 months, 12 patients remained claudication free with no evidence of obstructive arterial disease of the treated segment on imaging studies. One patient developed restenosis that was treated with repeat atherectomy and balloon angioplasty following which he was asymptomatic at follow-up. Conclusion: The use of directional atherectomy followed by balloon angioplasty is a quick, safe, and effective endovascular approach to treating Angio-Seal-associated femoral artery occlusions. It is associated with an excellent success rate, no complications, and good midterm outcomes.